An improved computational framework based on the dual boundary element method for three-dimensional mixed-mode crack propagation analyses. (September 2019) - Cordeiro, Sergio Gustavo Ferreira; Leonel, Edson Denner
Highlights: An improved computational framework based on the DBEM is presented for 3D crack propagation analyses; The input data scheme enables flexible meshing of complex NURBS surfaces geometries; The influence of the twisting angles is accounted into the mixed-mode crack propagation by a variational formulation; A linear approximation for the SIF range adopted to improve the accuracy of the discrete solution of the Paris-Erdogan equation. Abstract: This study presents an improved computational framework based on the Dual Boundary Element Method (DBEM) for modelling three-dimensional mixed-mode fatigue crack propagation in geometrically complex structural components. The improvements are: (i) an input data scheme based on an alternative collocation strategy, which enables the discretization of each Non-Uniform Rational B-splines (NURBS) surfaces of geometrical models without any concerning about conform meshes at the surface´s intersections. (ii) a variational formulation defined over the crack front, which accounts for both kinking and twisting angles of the during the crack propagation. (iii) a linear approximation for the Stress Intensity Factors (SIF) range, which was applied in the three-dimensional fatigue analysis and enables the discrete solution of the Paris law in accurate form. The SIF are assessed by the displacement correlation or extrapolation techniques. The maximum energy release rate or the Schöllmann's criteria are adopted for driving the propagation process. Four numerical examples are presented in order to validate the proposed computation framework and investigate its accuracy and robustness.